Cerebral Stroke Secondary to Decompression Ilness (DCI): Pathophysiology, Clinical Presentation, Diagnosis, and Management - Khairifathiyyah, Khairifathiyyah; Aryasta, Ida Bagus Putra Bayu; Prawira, I Nyoman Dio Yudha; Untari, Lania Pradiva; Pambudi, Balqis Prudena Kurnia; Hunaifi, Ilsa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Decompression illness (DCI) encompasses two major diving-related disorders: decompression sickness (DCS) and arterial gas embolism (AGE). Both conditions are characterized by the formation of gas bubbles that act as the primary mechanism of tissue injury, resulting in overlapping clinical manifestations and similar therapeutic approaches. This study aims to review the pathophysiology, clinical presentation, diagnosis, and management of DCI that presents with stroke-like neurological symptoms. The method used was a literature review approach based on current evidence from recent scientific publications. Findings show that DCS occurs when dissolved inert gases, such as nitrogen, become supersaturated during ascent and form bubbles within tissues and the venous circulation. AGE typically arises from pulmonary barotrauma, allowing trapped gas to enter the pulmonary veins and reach the arterial circulation, with the brain as the most vulnerable target organ. DCI is considered a medical emergency requiring definitive management with hyperbaric oxygen therapy (HBOT). Neurological manifestations of DCI often resemble conventional ischemic stroke but demonstrate distinct clinical and temporal patterns related to pressure changes. Therefore, in addition to recompression therapy, patients may require standard acute stroke management. Prognosis depends heavily on the promptness of diagnosis and treatment, as early intervention is critical to preventing permanent neurological injury.